Variability in the clinical practice of maintaining the patency of peripheral intravenous catheters Variabilidad en la práctica clínica del mantenimiento de la permeabilidad de catéteres venosos periféricos - Julio Cabrero; M. Isabel Orts; M. Luisa López-Coig; M. Luisa Velasco; Miguel Richart (Elsevier, 2005)
Objective: To establish variations in clinical practice associated with maintaining the patency of peripheral intravenous catheters (PIC) and to determine to what extent such clinical practice falls within the limits of the available scientific evidence, based on a random sample of Spanish public hospitals. Methods: A cross-sectional, descriptive study was carried out in non-psychiatric public hospitals and their associated medical and surgical units. Cluster (hospitals), stratified (hospital size), and single-stage (all units) sampling was applied. A questionnaire was mailed to all of the units involved. Results: A sample of 341 valid questionnaires was analysed (response rate 54.5%). Only one praxis-modality was carried out in the majority of units. Intermittent flushing and heparin saline versus normal saline was the most frequent modality employed, over those of continuous flushing and non-heparinised saline. There was a high degree of variation in the quantity of heparin administered: 81.7% when flushing was carried out with heparinised saline and 48.2% when it was conducted with concentrated heparin. About 40% of this variation was associated with the hospital in question, rather than with the unit. The clinical practice fell within the limits of available scientific evidence in fewer than half of the units studied. Conclusions: There was a high degree of variability in the practice of maintaining PIC patency. A significant part of this variation was attributable to the hospital in which the practice was carried out. Moreover, most of this practice was carried out beyond the limits of available scientific evidence. Objetivo: Determinar la variabilidad de la práctica clínica en el mantenimiento de la permeabilidad de los catéteres venosos periféricos en una muestra aleatoria de hospitales españoles y determinar en qué medida esta práctica se realiza dentro del rango de la evidencia disponible. Métodos: Estudio descriptivo y transversal. Ámbito y población: Hospitales públicos no psiquiátricos del Sistema Nacional de Salud y sus unidades médicas o quirúrgicas. Se realizó un muestreo por conglomerados (hospitales) estratificado (tamaño de los hospitales) y monoetápico (todas las unidades). Las variables se recogieron mediante un cuestionario administrado por correo postal. Resultados: Se recibieron 341 cuestionarios válidos (tasa de participación del 54,5%). En la mayoría de las unidades sólo se realiza una modalidad de la práctica. El lavado intermitente frente al lavado continuo y el suero salino con heparina frente al no heparinizado son las modalidades más frecuentes. Hay una elevada variabilidad en la cantidad de heparina administrada: el coeficiente de variación intercuartílico es del 81,7% si el suero es heparinizado y del 48,2% si es con una dilución de heparina dada. Alrededor del 40% de esta variabilidad es atribuible al hospital y no a la unidad. En menos de la mitad de las unidades la práctica se realiza de acuerdo con la evidencia actual. Conclusiones: Hay una gran variabilidad en la práctica del mantenimiento de la permeabilidad de los catéteres venosos periféricos. Una parte sustancial de esa variabilidad es incompatible con la evidencia actual, y una parte significativa de la variabilidad reside en el hospital donde se realiza la práctica.